2012
DOI: 10.1016/j.jep.2011.12.045
|View full text |Cite
|
Sign up to set email alerts
|

Differential signaling involved in Sutherlandia frutescens-induced cell death in MCF-7 and MCF-12A cells

Abstract: Ethnopharmacological relevance: The scientific study of natural products traditionally used in anticancer preparations has yielded several therapeutically relevant compounds. One of these traditional preparations with potentially beneficial properties is aqueous extracts of Sutherlandia frutescens, a shrub indigenous to the Western Cape region of South Africa. Classification:Malignant disease and immunosuppression

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Because this species has a strong reputation in folklore as a medicinal plant that treats cancers, studies to validate these claims are plenty. For example, some studies showed that extracts lead to apoptosis of breast cancer cell lines with MCF-7 tumor cells being more susceptible to cell death in comparison to the MCF-12 A cells [7,8]. They also inhibit growth of CaCo 2 colon cancer cells by disrupting cell membranes and cell death is mediated via the P13-K pathway [9].…”
Section: Introductionmentioning
confidence: 99%
“…Because this species has a strong reputation in folklore as a medicinal plant that treats cancers, studies to validate these claims are plenty. For example, some studies showed that extracts lead to apoptosis of breast cancer cell lines with MCF-7 tumor cells being more susceptible to cell death in comparison to the MCF-12 A cells [7,8]. They also inhibit growth of CaCo 2 colon cancer cells by disrupting cell membranes and cell death is mediated via the P13-K pathway [9].…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] Its ethanolic extract has been reported to induce a concentration-dependent anti-proliferative activity on human tumours including the SNO oesophageal cancer and MCF-7 breast cancer cell lines. 17,18 Similarly, its aqueous extract was also reported to induce cytotoxicity in both MCF-7 and MDAMB 231 breast cancer cell lines as well as in HL60 and Jurkat leukaemia cells. [18][19][20][21][22] More so, S. frutescens has been reported to show anti-cancer activity in prostate cancer as it induced cytotoxicity in human prostate cancer cells DU-145, PC3, LNCaP and mouse prostate cancer cell, TRAMP-C2.…”
Section: Introductionmentioning
confidence: 97%
“…17,18 Similarly, its aqueous extract was also reported to induce cytotoxicity in both MCF-7 and MDAMB 231 breast cancer cell lines as well as in HL60 and Jurkat leukaemia cells. [18][19][20][21][22] More so, S. frutescens has been reported to show anti-cancer activity in prostate cancer as it induced cytotoxicity in human prostate cancer cells DU-145, PC3, LNCaP and mouse prostate cancer cell, TRAMP-C2. 20,23 It also induced apoptosis and inhibited the PI3K-kinase cell survival pathway in CaCo2 colon cancer cells.…”
Section: Introductionmentioning
confidence: 97%
“…Sutherlandia frutescens, commonly known as the "cancer bush" by South African healers, is a medicinal plant traditionally used to treat many human diseases, including cancer (Van Wyk et al, 2002;Prevoo et al, 2004;Grandi et al, 2005;Chadwick et al, 2007;Van Wyk and Albrecht, 2008;Van Wyk, 2011). Ethanolic extract of S. frutescens showed dose-dependent anti-proliferative and apoptotic effects on several human tumors including the breast cancer cell line MCF-7 (Vorster et al, 2012). A similar inhibition can also be achieved by aqueous extract (Tai et al, 2004;Steenkamp and Gouws, 2006;Stander et al, 2009;Vorster et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…frutescens showed dose‐dependent anti‐proliferative and apoptotic effects on several human tumors including the breast cancer cell line MCF‐7 (Vorster et al, ). A similar inhibition can also be achieved by aqueous extract (Tai et al, ; Steenkamp and Gouws, ; Stander et al, ; Vorster et al, ). Chinkwo () demonstrated that an aqueous extract induced cellular apoptosis in cervical carcinoma and Chinese hamster ovary (CHO) cells.…”
Section: Introductionmentioning
confidence: 99%